Determining The Shortest Path In Car Parking Layout In FMIPA UNPAD Using Floyd-Warshall Algorithm - Suyudi, Mochamad; Mardiyah, Asma Ainun (iora, 2022)
Vehicles that are increasingly needed by the community increase the volume of vehicle traffic, resulting in a high demand for parking spaces. Especially in public places such as campuses, offices, shopping centers, and other places. A parking lot is also needed that has a maximum capacity by determining the layout of the vehicle mileage in finding a parking location. In this paper, we are looking for the shortest path in the car park layout at FMIPA UNPAD using the Floyd-Warshall algorithm.